Baicalin attenuates vascular inflammation and endothelial dysfunction in diabetes - Lingchao Miao; Yifan Yang; Jinming Dai; Mei Bai; Yuehan Wang; Haiying Cui; Lin Lin; Metab Alharbi; Wai San Cheang (Food Frontiers)
Abstract Baicalin is a natural flavonoid shown to attenuate inflammation, tumor, and cardiovascular diseases. However, its effect on endothelial function in diabetes remains unclear and was investigated in current study. A high‐fat diet (60% kcal fat diet) was used to feed male C57BL/6 mice for 14 weeks to build a diet‐induced obese (DIO) diabetic mouse model. Baicalin (50 and 100 mg/kg/day) or vehicle was applied to DIO mice by oral gavage in the last 4 weeks. Separated mouse aortic rings were induced by high glucose and primary rat aortic endothelial cells (RAECs) were stimulated by advanced glycation end products (AGEs), and cotreated with or without varying doses of baicalin and 5′AMP‐activated protein kinase (AMPK) inhibitor Compound C. Forty‐eight‐hour exposure to high glucose impaired acetylcholine‐induced endothelium‐dependent relaxations in mouse aortas and produced excessive levels of reactive oxygen species (ROS). Similar phenomenon was observed in aortas from DIO mice. Baicalin treatment could alleviate these damage through preventing expression and translocation of nuclear factor (NF)‐κB p65 pathway, accomplished with decreased expressions of vascular cell adhesion molecule 1 (VCAM‐1) and intracellular adhesion molecule 1 (ICAM‐1) as well as proinflammatory cytokines including tumor necrosis factor alpha (TNF‐α) and interleukin 6 (IL‐6). These improvements were AMPK‐dependent as Compound C abolished the effects. Similar beneficial effects of baicalin and inhibitory effects of Compound C were observed in AGEs (200 µg/mL, 24 h)‐induced RAECs. To conclude, baicalin protects against vascular inflammation and endothelial dysfunction associated with diabetes through suppression on inflammation and oxidative stress via activating AMPK.